Cortical excitability and the aging brain: toward a biomarker of cognitive resilience - Palermo, Sara; Di Fazio, Chiara; Scaliti, Eugenio; Stanziano, Mario; Nigri, Anna; Tamietto, Marco (Frontiers in Psychology, 2025)
This perspective article addresses the potential use of cortical excitability (CE) as an indicator of cognitive health in aging people. Changes in CE may be considered a sign of resilience to cognitive decline in old age. The authors describe research on CE and its link to cognitive function in older adults and emphasize that it is a promising, non-invasive measure of healthy aging. They also address the current challenges in its implementation, the need for standardized measurement protocols and possible future avenues of research. If properly considered, CE could pave the way for early detection of cognitive decline and facilitate targeted interventions to promote cognitive resilience.